Naturally occurring antibodies that recognize linear epitopes in the amino terminus of the Hepatitis C virus E2 protein confer noninterfering, additive neutralization - Tarr, Alexander, W.; Urbanowicz, Richard, A.; Jayaraj, Dhanya; Brown, Richard, J.P.; McKeating, Jane, A.; Irving, William L.; Ball, Jonathan, K. (American Society for Microbiology, 2012)
Chronic hepatitis C virus (HCV) infection can persist even in the presence of a broadly neutralizing antibody response. Various mechanisms that underpin viral persistence have been proposed, and one of the most recently proposed mechanisms is the presence of interfering antibodies that negate neutralizing responses. Specifically, it has been proposed that antibodies targeting broadly neutralizing epitopes located within a region of E2 encompassing residues 412 to 423 can be inhibited by nonneutralizing antibodies binding to a less conserved region encompassing residues 434 to 446. To investigate this phenomenon, we characterized the neutralizing and inhibitory effects of human-derived affinity-purified immunoglobulin fractions and murine monoclonal antibodies and show that antibodies to both regions neutralize HCV pseudoparticle (HCVpp) and cell culture-infectious virus (HCVcc) infection albeit with different breadths and potencies. Epitope mapping revealed the presence of overlapping but distinct epitopes in both regions, which may explain the observed differences in neutralizing phenotypes. Crucially, we failed to demonstrate any inhibition between these two groups of antibodies, suggesting that interference by nonneutralizing antibodies, at least for the region encompassing residues 434 to 446, does not provide a mechanism for HCV persistence in chronically infected individuals.